Familial myasthenia gravis: report of four cases - José Lamartine de Assis; Milberto Scaff (Arquivos de Neuro-Psiquiatria)
Two pairs of siblings with myasthenia gravis, belonging to two different families, are reported. This is the only record of familial myasthenia during the past twenty years, in a total of 145 patients seen at the Neurological Clinic of the São Paulo Medical School. In spite of the fact that myasthenia gravis does not show hereditary characteristics, the peculiar features of the four cases justify the present report. The two pairs of siblings were born from non myasthenic nor consanguineous parents. The disease started at birth showing bilateral partial eyelid ptosis in all patients. The course of the illness has been favorable. There was no thymoma.